Bioaerosols in the Food and Beverage Industry - Theisinger, Shirleen M.; de Smidt, Olga (Intech Open: Ideas and Applications Toward Sample Preparation for Food, 2017)
Bioaerosol monitoring is a rapidly emerging area of industrial hygiene. Microbial roles in atmospheric processes are thought to be species specific and potentially depend on cell viability. Accumulating evidence suggests that exposure to bioaerosols may cause adverse health effects, including disease. Studies of bioaerosols have primarily focused on chemical composition and biological composition, and the negative effects thereof on ecosystems and human health have largely gone unnoticed. This gap can be attributed to international standards on acceptable maximum bioaerosol loads not being uniform and the lack of uniform standardized methods for collection and analysis of bacterial and fungal bioaerosols. In this chapter, bioaerosol composition, relevance of bioaerosols to the food processing facility, sampling and detection approaches, and complications were discussed.
Published Book Chapter
Keywords: bioaerosols; microbial diversity; passive/active sampling; food handler health